“Se llamaría Colombia”. Una relectura de la Carta de Jamaica, 1815 (Dossier: El momento colombiano de las repúblicas andinas. Desde el concepto de Colombia hasta el reconocimiento internacional) - Arroyo, Isabel Cristina (2021)
The Letter from Jamaica, written in 1815, is commonly referred as the document in which the Liberator enshrined his dream for Latin American unity. That interpretation, however, comes from readings made in subsequent contexts, not from the text itself or the document’s original intent. The present article undertakes to reread the Letter taking into consideration the time of breakup and uncertainty when it was written, viewed not only from the standpoint of Bolívar himself but also from the standpoint of the peoples who, were incorporated into the republic that “would be called Colombia”. It is argued that the Letter’s historical novelty and importance does not lie in the proposal for Spanish-American unity. It is the limitation of the territorial scope of the Colombian project to build a centralized republican state that led to a radical break from the imperial order.